O reino de Portugal e o bloqueio napoleónico - Azeredo, Carlos de (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
The British naval victories of Cape St. Vincent, Aboukir and Trafalgar prompted the annihilation of Napoleon’s naval capability, and compelled him to seek the ruin of Great-Britain’s economy by imposing what became known as the Continental System. Consequently, after signing the Treaty of Tilsit, the French Emperor turned his attention to Portugal, as the country defied the blockade by keeping its sea ports open to trade with the English. Before 1806, however, Napoleon already planned invading and taking control over Portugal, as his correspondence can confirm. By the early 19th century, Portugal was still one the worlds’ maritime powers, although it remained neutral to maintain good relationships with England, as well as with France and Spain. London reacted against Napoleon’s impositions by declaring an embargo against France and its allies. There is some evidence that the Berlin Decree was a pretext to invade and take possession of Portugal, to maintain a strong alliance with Spain, to take over the more powerful Portuguese fleet and incorporate it under the French flag, to give access to the French fleet to the port of Lisbon and stop the Portuguese wine trade with England.